Streamlining event extraction with a simplified annotation framework - Saetia, Chanatip; Thonglong, Areeya; Amornchaiteera, Thanpitcha; Chalothorn, Tawunrat; Taerungruang, Supawat; Buabthong, Pakpoom (Frontiers in Artificial Intelligence, 2024)
Event extraction, grounded in semantic relationships, can serve as a simplified relation extraction.In this study, we propose an efficient open-domain event annotation framework tailored for subsequent information extraction, with a specific focus on its applicability to low-resource languages. The proposed event annotation method, which is based on event semantic elements, demonstrates substantial time-efficiency gains over traditional Universal Dependencies (UD) tagging. We show how language-specific pretraining outperforms multilingual counterparts in entity and relation extraction tasks and emphasize the importance of task-and language-specific fine-tuning for optimal model performance. Furthermore, we demonstrate the improvement of model performance upon integrating UD information during pre-training, achieving the F1 score of 71.16% and 60.43% for entity and relation extraction respectively. In addition, we showcase the usage of our extracted event graph for improving node classification in a retail banking domain. This work provides valuable guidance on improving information extraction and outlines a methodology for developing training datasets, particularly for low-resource languages.